Removal of denture adhesives from PMMA and Polyamide denture base materials (Journal of Applied Oral Science, 2021)
Denture adhesives need complete removal due to their frequent replacement. Objective: Our study investigates the removal of denture adhesives from denture base materials, using different methods. Methodology: PMMA and Polyamide denture base materials were used to fabricate 120 samples (15×15×1.5mm). One side of the samples was left as processed and the other polished with a usual procedure, hydrated for 24 h, dried, and weighted. They received 0.2 g of three adhesive creams on their unpolished surface (Corega, Olivafix, Fittydent), pressed on polysulfide material, stored under 37°C and 95% rel. humidity for 1 h and 60 of them, following their separation from polysulfide base, brushed under running water, whereas the rest inserted in a cleanser bath (Fittydent Super) for 5 min. The samples were dried and inserted in the oven (37°C) for additional 10 min and weighted again. Roughness tests of denture materials and light microscopy of adhesives creams were also used to evaluate the materials. Time lapse images of spayed with water adhesives on PMMA base were also taken to evaluate the volumetric changes of adhesives. Weight data before and after adhesive removal, indicating the amount of remaining adhesive, were statistically analyzed using Welch’s ANOVA and Games-Howell multiple comparisons tests at α=0.05 level of significance. Results: Roughness of Polyamide was higher than PMMA and Fittydent showed greater volumetric changes than the others. Significant differences (p<0.05), were found between PMMA and Polyamide bases, between Olivafix and Fittydent adhesives, and between brushing and cleansing methods but only for PMMA-Olivafix combination. Conclusions: Adhesives showed a stronger adherence to PMMA surface, and Fittydent was the most difficult to be removed. Removal methods were not effective for all adhesives or denture base materials. These indicate that removal methods, adhesive type and denture base material are all playing a significant role in the removal of adhesives from denture surfaces.